Multiparametric MRI assessment of renal blood oxygenation, fat content, and hemodynamics in an animal model of metabolic dysfunction-associated steatotic liver disease - Wang, Chao; Qin, Jiaming; Yuan, Hongtao; Zhou, Jin; Cao, Ting; Zhu, Jinxia; Kang, Simeng; Xie, Shuangshuang; Shen, Wen (Frontiers in Endocrinology, 2025)
AimsMetabolic dysfunction-associated steatotic liver disease (MASLD) is a significant risk factor for chronic kidney disease. There is a lack of an accurate and comprehensive technique for detecting MASLD-related renal injury. This study aims to evaluate the efficacy of arterial spin labeling (ASL), blood oxygen level-dependent (BOLD) imaging, and proton density fat fraction (PDFF) for assessing renal injury in an animal model of MASLD.MethodsAn animal model of MASLD was established using a high-fat diet. Forty-nine 6-week-old male Sprague-Dawley rats were divided into the pathology (14, 16, 18, 20, 22, and 24 weeks, n = 7 per subgroup) and continuous-scanning (n = 7) groups. Renal alterations at different time points were quantified through the application of ASL-renal blood flow (RBF), BOLD-T2*, and Fat Fraction (FF), alongside pathological indices and blood biochemical markers.ResultsRBF did not change significantly from 14–24 weeks, consistent with the peritubular capillary density. Compared with those at week 14, renal T2* significantly decreased at week 20, FF increased at week 20, and serum creatine levels increased at week 24. Renal T2* and FF were significantly correlated with renal H&E scores and HIF-1α expression (|r| = 0.3552–0.7745). Kidney BOLD-T2*, liver and kidney FF enabled detecting renal injury in an animal model of MASLD (area under the curve = 0.76–0.86).ConclusionDuring fatty liver disease progression, renal blood oxygen levels decreased, fat deposition increased, and blood flow remained unchanged. BOLD and PDFF allowed accurately quantifying these changes to facilitate early detection of kidney injury.